Oenothein B inhibits human non-small cell lung cancer A549 cell proliferation by ROS-mediated PI3K/Akt/NF-κB signaling pathway. (25th January 2019) - Pei, Xiaodong; Xiao, Junsong; Wei, Guijiang; Zhang, Yumeng; Lin, Feng; Xiong, Zhaocheng; Lu, Lan; Wang, Xueli; Pang, Guangfu; Jiang, Yan; Jiang, Lihe
Abstract: Oenothein B has a wide range of biological activities. The present study probed into the underlying mechanism on how Oenothein B inhibits the proliferation of a lung cancer line A549. Our results showed that Oenothein B effectively inhibited the proliferation of A549 cells by inducing apoptosis and arresting cells at G1 stage. Furthermore, Oenothein B not only increased the level of intracellular reactive oxygen species (ROS), but also induced the upregulation of intracellular apoptotic triggers (cleavage caspase-3, PARP, cytochrome c level in the cytosol, Bax). Moreover, ROS inhibitor (N-acetyl-L-cystein, NAC) and PI3K agonist (Insulin-like growth factor 1, IGF-1) could resist cell proliferation inhibition induced by Oenothein B, respectively. ROS inhibitor significantly abrogated the activation of caspase 3/7 and 9 in the presence of Oenothein B. Additionally, suppression of p-PI3K and p-Akt, p-NF-κB by Oenothein B could be compensated by treatment with ROS inhibitor. To summarize, these results demonstrated that Oenothein B was able to prevent cell proliferation probably via ROS-mediated PI3K/Akt/NF-κB signaling pathway. Graphical abstract: Highlights: Oenothein B increases the level of ROS and induces some apoptotic proteins expression. ROS inhibitor and PI3K agonist could resist cell proliferation inhibition induced by Oenothein B, respectively. The protein levels of p-PI3K and p-Akt, p-NF-kB suppressed by Oenothein B could be offset by ROS inhibitor. Oenothein B can prevent cell proliferation maybe via ROS-mediated PI3K/Akt/NF-kB signaling pathway.